2006
DOI: 10.1002/hyp.6219
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved rainfall inputs and streamwater outputs in an undisturbed watershed on highly weathered soils in the Brazilian cerrado

Abstract: Abstract:The cerrados of Brazil cover 2 million km 2 . Despite the extent of these seasonally dry ecosystems, little watershed research has been focused in this region, particularly relative to the watersheds of the Amazon Basin. The cerrado shares pedogenic characteristics with the Amazon Basin in draining portions of the Brazilian shield and in possessing Oxisols over much of the landscape. The objective of this research was to quantify the stream water geochemical relationships of an undisturbed 1200 ha cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 60 publications
6
25
0
1
Order By: Relevance
“…The measured low water conductivity (<10 µS·cm -1 ) supported previous studies at deeply weathered, weakly buffered Cerrado sites (Markewitz et al, 2006;Parron, 2004;Silva et al, 2011;Wantzen, 2003). We expected electrical conductivity to increase due to inverse dilution effects (i.e.…”
Section: Impact Of Agriculture On Water Qualitysupporting
confidence: 86%
“…The measured low water conductivity (<10 µS·cm -1 ) supported previous studies at deeply weathered, weakly buffered Cerrado sites (Markewitz et al, 2006;Parron, 2004;Silva et al, 2011;Wantzen, 2003). We expected electrical conductivity to increase due to inverse dilution effects (i.e.…”
Section: Impact Of Agriculture On Water Qualitysupporting
confidence: 86%
“…Therefore, the concentration of dissolved oxygen was higher in streams located in Capão Bonito followed by streams in Teodoro Sampaio and Piracicaba and Santa Rita do Passa Quatro ( Figure 3). The values found in stream 6 (located at Santa Rita do Passa Quatro) were lower if compared to other streams in state parks since this area is located under savanna region with presents highly weathered soils and poor nutrient concentrations (Markewitz et al 2006) that reflected in all parameters of water chemistry evaluated in this work (see above). Silva et al (2007) evaluating undisturbed stream in this area reported that land use changes such as sugar cane and eucalyptus contribute to a decrease of physicochemical conditions in savanna watersheds.…”
Section: Streamwater Chemistrymentioning
confidence: 60%
“…Low ion concentrations previously observed in Cerrado region streams under natural cover are a result of the highly weathered soils and their associated low nutrient concentrations (Markewitz et al 2006). Given these low background concentrations, it was hypothesized that increases in dissolved solute loads under anthropogenic land covers would be readily observed.…”
Section: Discussionmentioning
confidence: 98%